(untitled) (Zia e Tahqeeq, 2025)
Issues regarding rejection of Hadith literature as a source of Shariah was found in second century of hijri when Khawarij and Mutazili raised questions on the authenticity of Hadith. Scholar of hadith responed the questions about authenticity of hadith. After that Muslims unanimously accepted Hadith as a primary source of Shariah and moral teaching of Islam. In 19th and 20th century with the advent of colonialism and under the umbrella of Orientalists the issues again raised abouth the authenticity of Hadith by some muslim scholars of subcontinent. This article mainly focus on commonalities between Orientalists approach and Muslim deniers of Hadith, with special reference to Joseph Schacht and Ghulam Ahmad Pervez.